[English original] Effectiveness of goalball athletes throwing in the Chilean National League - Campos Campos, Kevin Isaías (2021)
Goalball is a collective Paralympic sport with oppositional characteristics but without invasion by the athletes that, despite requiring great physical condition in offensive and defensive actions, is also identified as a tactical sport, where the administration of technique in the various game situations determines success in competition. The objective of the study was to analyze the effectiveness of the attack of the Chilean National Goalball League, according to type of shot and trajectory. Four Goalball matches of the final phase of a national tournament were filmed. For this, a digital camera was used behind an arch located in height. The matches were analyzed following the diagrams proposed by Morato et al. (2016) and Morato (2012). The front throw (FRO) was used the most (88.9%) with an effectiveness rate of 6.2%. Longer trajectories were made in short diagonals (SD) and parallel (PA) (31.3% and 23.2%, respectively). The FRO throw was directed in SD (34.5%) and PA (22.4%), while on the other hand, the spinning throws (SP) were directed preferably in PA (30.4%) and SD (29.1%). The FRO throw was more effective in PA (10.6%), whereas the SP throw was more effective in the middle diagonal (MD) (12.5%). The lateral positions execute throws, preferably FRO, but in defense the central positions are protagonists. Throws are most effective when they are directed in PA and SD.